A critical review on in situ reduction of graphene oxide during preparation of conducting polymeric nanocomposites. Issue 41 (7th May 2015) - Mural, Prasanna Kumar S; Sharma, Maya; Madras, Giridhar; Bose, Suryasarathi
<x xml:space="preserve">Abstract</x> In situ reduction of graphene oxide during preparation of conducting polymeric nanocomposites.